Husseini rituals and their impact on tourism movement – the Arbaeen pilgrimage as a model (Czech Journal of Multidisciplinary Innovations, 2025)
The Husseini rituals constitute the identity of the Islamic nation, the voice of truth, the defense of freedom, and the purification of souls from negative thoughts. The Husseini rituals serve as an intellectual, ideological, and educational institution that encompasses the greatest lessons in morality and culture while also acting as a voice of truth. Through these rituals, a culture of religious tourism can be instilled in society, with the most important of these being the Arbaeen pilgrimage. The Arbaeen pilgrimage has become a unique event in recent years, representing the primary destination for religious tourism, with millions of Muslims flocking there annually to participate in the pilgrimage and its various accompanying activities, which can enhance the tourism sector. The Arbaeen pilgrimage has a direct impact on tourism movement, contributing to the improvement of the economic, social, cultural, and educational sectors. In addition, it can be an important source of hard currency, increase the workforce, and boost national income. The overall objective of this research is to understand the impact of Husseini rituals on tourism movement from the economic, social, and organizational aspects of the millions-strong pilgrimage (the Arbaeen pilgrimage as a model). To ensure the study's requirements are met, the study population consisted of (300) questionnaires distributed to a random sample of visitors to the city of Karbala during the Arbaeen pilgrimage